Modern Technique and Technologies. MTT 2010: Proceedings of the 16th International Scientific and Practical Conference of Students, Post-graduates and Young Scientists, April 12 - 16, 2010 Tomsk, Russia (Tomsk, TPU Press, 2010)
Copyright and Reprint Permission: Abstracting is permitted with credit to the source. Libraries are permitted to photocopy beyond the limit of U.S. copyright law for private use of patrons those articles in this volume that carry a code at the bottom of the first page, provided the per-copy fee indicated in the code is paid through Copyright Clearance Center.